Manifestation of unusual size effects in granular thin films prepared by pulsed laser deposition - Sergeenkov, S.; Cichetto, L. [UNESP]; Diaz, J. C.C.A.; Bastos, W. B. [UNESP]; Longo, E. [UNESP]; Araújo-Moreira, F. M. (Elsevier, 2016)
We demonstrate manifestation of some rather unusual size effects in granular thin films prepared by a pulsed laser deposition technique. We observed that the temperature dependence of resistivity ρ(T) notably depends on the relation between the grain size Rg and the film thickness d. Namely, more granular LaNiO3 thin films (with small values of Rg) grown on LaAlO3 substrate are found to follow a universal ρ(T)∝T3/2 law for all the measured temperatures. While less granular thin films (with larger values of Rg), exhibit a more complicated behavior accompanied by a clear-cut crossover (around Tcr=200K), from ρ(T)∝T3/2 (for 20K<T<200K) to ρ(T)∝T (for 200K<T<300K). The obtained results are attributed to manifestation of the finite temperature size effects (when an average grain size Rg becomes comparable with the thermal de Broglie wavelength Λ) leading to the crossover temperature Tcr∝ (d/Rg)2.
Keywords: Crossover; Nickelates; Pulsed laser deposition; Resistivity; Thin films